Strategi Amerika Serikat dalam Menekan Pengembangan Nuklir Iran - Rio Sundari (Frequency of International Relations (FETRIAN), 2020)
The purpose of this research “United States strategy in Suppressing Iran's Nuclear Development” as a critical analysis related to the controversy over nuclear development conducted by Iran. In the history of Iran's nuclear development, the United States is one of the countries that fully support this nuclear development. However, the dynamics of relations between Iran and the United States are a factor in the status of nuclear development. As a result, Iranian attitudes and policies that are not in line with the United States will result in a decline in American support for Iran’s nuclear development. Finally, in 2018 the US announced its exit from the Joint Comprehensive Plan of Action (JCPOA) and decided to impose economic sanctions on Iran which coincided with Iranian support for Syria which was contrary to US political attitudes. This research uses qualitative research methods using secondary data such as books, journals, articles, and other sources to provide analysis of this case. This research results in a finding of efforts and strategies carried out by the United States to suppress Iran’s nuclear development. This was done because of two things, first, related to the interests of the United States in the Middle East. Iran’s political stance is often at odds with the politics of the United States. Second, reduce and maintain the hegemony of Israel as a close ally of the United States in the Middle East.